WATER INTAKE APPLET BASED ON HUMAN EXCREMENT - Swastika, Nadine; Hasuki, Winda; Savero, Sava; Satya, Putri Gabriella; Parikesit , Arli Aditya (Kresnamedia Publisher, 2021)
To function properly, the human body requires adequate hydration as 70% of the human body was being built up by water. It acts as a solvent for lots of biochemical reactions to keep our physiological function work optimally throughout the day. Dehydration could cause a disturbance in both the gastrointestinal and kidney systems of human beings, and it could be noticed in the color of both urine and feces. The objective of this paper is to present an idea on how to make a water intake app based on the color indicator of human excrement surveillance. It might be a solution to intensify people's ability to become self-conscious when drinking less water by surveying the excreted substance. The deployed method is to measure one indicator which is between urine and feces detector on how much water should the user drink by observing the color of both their urine and feces. However, both excrement indicators are needed to detect users' drinking amount. If one of these indicators shows a bad result, it could lead to water intoxication or hydration. The application has been successfully created using Python to give feedback for the user's water intake based on the condition of their excreted substance. The Water Intake application has successfully shown a clear indicator for dehydration. It could be inferred that this water intake software could detect the dehydration phenomenon with human excrement as the main indicator.